2011
DOI: 10.1007/978-3-642-22362-4_15
|View full text |Cite
|
Sign up to set email alerts
|

Open Social Student Modeling: Visualizing Student Models with Parallel IntrospectiveViews

Abstract: Abstract. This paper explores a social extension of open student modeling that we call open social student modeling. We present a specific implementation of this approach that uses parallel IntrospectiveViews to visualize models representing student progress with QuizJET parameterized self-assessment questions for Java programming. The interface allows visualizing not only the student's own model, but also displaying parallel views on the models of their peers and the cumulative model of the entire class or gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 7 publications
(14 reference statements)
0
25
0
5
Order By: Relevance
“…The growth of sessions can be attributed to the progress ranking feature, which is intended to create a positively motivating and yet competitive platform. Moreover, in our subjective evaluation [17], most of the students (84.6%) appreciated the feature of comparing their progress with others. They liked the interface and found it easy to use (92.3%).…”
Section: Evalumentioning
confidence: 90%
“…The growth of sessions can be attributed to the progress ranking feature, which is intended to create a positively motivating and yet competitive platform. Moreover, in our subjective evaluation [17], most of the students (84.6%) appreciated the feature of comparing their progress with others. They liked the interface and found it easy to use (92.3%).…”
Section: Evalumentioning
confidence: 90%
“…As shown in Figure 1 Another difference is in the topic page, as shown in Figure 1 (b). The second version of Topolor provides graphical and interactive pop-up views of learners' performance (e.g., quiz scores) and contribution (e.g., the number of questions answered), supported by the newly introduced open social student modelling [16] component. The interactive visualisation of performance and contribution allows learners to operate multi-context comparisons (i.e., in the context of a specific course or a specific topic) as well as multi-group comparisons (i.e., compare to another learner, top 20% learners, or all other learners).…”
Section: Overview Of the 2nd Version Of Topolormentioning
confidence: 99%
“…A growing number of researchers have been working on facilitating e-learning environments by introducing a social dimension [29]. For instance, there is a great deal of research on social interaction tools for e-learning [27,33], learning behaviour analysis [31] and open social student modelling [16]. The in-progress results have indicated that users tend to be more motivated towards contributing to creating effective learning environment and enriching learning experiences in SNS-based e-learning [9].…”
Section: Introductionmentioning
confidence: 99%
“…A key issue that emerged was that students had difficulty connecting the course structure and the treemap layout. We improved the design by providing a clear sequence in progressing through the topics in Parallel IntrospectiveViews [36] and Progressor [34] studies. We discovered that students benefited from the guidance offered by the course structure and explored more diverse topics that were appropriate for them at the moment.…”
Section: Progressor + -An Open Social Student Modeling Interfacementioning
confidence: 99%
“…As we discovered, it is also important to offer a holistic view of individual student progress. In the Parallel IntrospectiveViews [36] study, we utilized the concept of unity, which proposed that perception of identity is higher if the model represents unity. This concept makes the students identify themselves with the model and allows them to easily compare themselves each other [12,13].…”
Section: Progressor + -An Open Social Student Modeling Interfacementioning
confidence: 99%